1991
DOI: 10.1007/bf00120829
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antiarrhythmic drugs on canine ventricular arrhythmia models: Which electrophysiological characteristics of drugs are related to their effectiveness?

Abstract: In order to compare and clarify the effects of various antiarrhythmic drugs when given as monotherapy, we reevaluated our previous data on antiarrhythmic drugs and recalculated antiarrhythmic plasma concentrations of drugs for several canine arrhythmia models. We used three spontaneously occurring arrhythmias: a) digitalis-, b) two-stage coronary ligation-, and c) adrenaline-induced arrhythmias. All antiarrhythmic drugs of class I suppressed digitalis arrhythmia, and, except for lidocaine, also suppressed coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 33 publications
4
28
0
Order By: Relevance
“…OPC-18790 had no deleterious effect on the digitalis VT, and it is consistent with our previous proposal that the occurrence of digitalis VT is not influenced by the Ca channel activities (11,13). The practical importance of this result is that this new positive inotropic agent can be used in combination with digitalis without increasing the risk of arrhythmia, and this is a common observation among new positive inotropic drugs in our previous study (6).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…OPC-18790 had no deleterious effect on the digitalis VT, and it is consistent with our previous proposal that the occurrence of digitalis VT is not influenced by the Ca channel activities (11,13). The practical importance of this result is that this new positive inotropic agent can be used in combination with digitalis without increasing the risk of arrhythmia, and this is a common observation among new positive inotropic drugs in our previous study (6).…”
Section: Discussionsupporting
confidence: 90%
“…Our previous experiments using three VT models showed that coronary ligation-induced and digitalis-induced VTs are Na channel-dependent, because they are suppressed by class I antiarrhythmic drugs, while adrenaline VT is Ca channel-dependent, because it is suppressed by class II 8-blockers and class IV Ca channel blockers (13). Like other new positive inotropic agents (6, 7), which are phos phodiesterase inhibitors and increase cardiac Ca current, OPC-18790 was shown to aggravate adrenaline VTs.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously described the use of the classical digitalis-induced and coronary ligation-induced arrhyth mia models to assess the antiarrhythmic activity of class I drugs (11). Correlation between EDSO(IVCT) in this study and antiarrhythmic effects on the in vivo canine digitalis arrhythmia of class I drugs expressed by the anti arrhythmic IC50 plasma concentrations from our earlier reports (11) is shown in Fig.…”
Section: Effects Of Ttx and Verapamil On Ivct Cbf And Dtmentioning
confidence: 78%
“…Other drugs were tested at 500-msec driving interval. An tiarrhythmic plasma concentrations were calculated from our earlier reports (11,39,40). P: procainamide, D: disopyramide, L4: lido caine at 400-msec driving interval, L3: lidocaine at 300-msec driving interval, M4: mexiletine at 400-msec driving interval, M3: mexiletine at 300-msec driving interval, F: flecainide, ME: ME3202, AN: AN 132.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation